A comparative approach to quantifying provision of acute therapy services. Issue 40 (8th October 2021) - Capo-Lugo, Carmen E.; Askew, Robert L.; Boebel, Matthew; DeLeo, Christine; Deutsch, Anne; Heinemann, Allen
Abstract : Abstract: This study aims to compare delivery of acute rehabilitation therapy using metrics reflecting distinct aspects of rehabilitation therapy services. Seven general medical-surgical hospitals in Illinois and Indiana prospectively collected rehabilitation therapy data. De-identified data on all patients who received any type of acute rehabilitation therapy (n = 35, 449) were extracted and reported as aggregate of minutes of therapy services per discipline. Metrics included therapy types, total minutes, and minutes per day (intensity), as charted by therapists. Extended hospital stay was defined as a length of stay (LOS) longer than Medicare's geometric mean LOS. Discharge destination was coded as postacute care or home discharge. Substantial variability was observed in types, number of minutes, and intensity of therapy services by condition and hospital. The odds of an extended hospital stay increased with increased number of minutes, increased number of therapy types, and decreased with increased rehabilitation intensity. This comparative approach to assessing provision of acute therapy services reflect differential effects of service provision on LOS and discharge destination. Investigators, policymakers, and hospital administrators should examine multiple metrics of rehabilitation therapy provision when evaluating the impact of health care processes on patient outcomes.